Efektivitas Instruksi Kerja Variasi Waktu Pemakaian Rompi sebagai Terapi Keluhan Nyeri Otot pada Pekerja Lunch Box di Bantul - Rahmawati, Nishfia; Yamtana, Yamtana; Kasjono, Heru Subaris (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2024)
A vest as therapy is a vest that can be used to reduce work fatigue in workers and improve posture in lunch box workers. Based on a preliminary study conducted on July 30, 2023, using the Nordic Body Map questionnaire to measure pain levels in 28 body locations. The questionnaire was conducted by interviewing 10 lunch box workers. One method used for vest intervention as therapy is to wear the vest on workers with time variations of 10, 15, and 20 minutes. Objective: to determine the effectiveness of work instructions for varying the time of wearing a vest as a therapy for the application of musculoskeletal pain complaints in Lunch Box workers at CV Tunas Jaya Abadi Bantul. Method: This study is a Quasi Experiment with a Pretest-Postest with Control Group Design approach. The number of research objects is 60 respondents. Results: The decrease in musculoskeletal pain complaints with a time variation of 10 minutes was 17.07%, a time variation of 15 minutes was 45.68%, and a time variation of 20 minutes was 73.75%. Based on the results of the One Way Anova test with Asymp.Sig of 0.000 < p value (0.05). Conclusion: The variation of the work instruction time for wearing a vest as the most effective therapy in the application of musculoskeletal pain complaints is at a time variation of 20 minutes.